The Role of Youth Organizations in Lempur Hilir Village, Gunung Raya District, Kerinci Regency - Amri, Faisal (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The role of youth is very important and is often associated with the progress of a nation. This has happened since the time of the Indonesian independence struggle, including the history of the youth oath declaration which is one proof that Indonesian youth have an important role in the role of the nation's struggle. In Permensos No. 25 of 2019, Karang Taruna in carrying out its duties is based on Pancasila and the 1945 Constitution, where Karang Taruna is an organization formed by the community as a potential and source of social welfare and the authority of Karang Taruna is to develop the potential of the younger generation and the community. From the description and description above, the author conducted research in Lempur Hilir Village, Gunung Raya District, which is stated in the research title The Role of Karang Taruna in Lempur Hilir Village, Gunung Raya District, Kerinci Regency. This type of research is normative juridical by studying various literature and legislation, as well as legal theories regarding the role and function of Karang Taruna in Lempur Hilir Village. The research approach methods used include, Conceptual Approach, Statute Approach, and Case Approach. The role of Karang Taruna in Lempur Hilir Village has been running well but has not been running optimally. This is due to various indicators, especially in making decisions on the vision and mission of Karang Taruna.